2000
DOI: 10.1024/0300-9831.70.5.238
|View full text |Cite
|
Sign up to set email alerts
|

Does a 100-km Walking Affect Indicators of Vitamin Status?

Abstract: The status of thiamin (B1), riboflavin (B2), ascorbic acid (AA), and tocopherol was determined in 60 leisure athletes (age 46 +/- 10 y, BMI 23.7 +/- 2.0 kg.m-2, VO2max 39.4 +/- 6.5 ml.min-1.kg-1), who completed a 100-km walking race. Vitamin plasma levels and activities of erythrocyte transketolase (ETK) and glutathione reductase (EGR) were measured before start, immediately after finishing and 6 hours later. The participators finished the entire distance in 14.25 h (average speed 7 km.h-1). Before start, all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 0 publications
4
8
1
Order By: Relevance
“…The first finding implies that a short-term exercise intervention on the day prior to blood sampling does not affect the reliability of using EGRAC for vitamin B2 status determination. Moreover, our observations are similar to previous findings [21,28,30]. Ohno et al [30] demonstrated in 11 untrained males (age 20.3 ± 0.3 y) that a single bout of exercise (30-min cycling test at 75% VO 2 peak) significantly increased FAD-stimulated EGR activity and non-significantly increased unstimulated EGR activity [30], but EGRAC values were lacking.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The first finding implies that a short-term exercise intervention on the day prior to blood sampling does not affect the reliability of using EGRAC for vitamin B2 status determination. Moreover, our observations are similar to previous findings [21,28,30]. Ohno et al [30] demonstrated in 11 untrained males (age 20.3 ± 0.3 y) that a single bout of exercise (30-min cycling test at 75% VO 2 peak) significantly increased FAD-stimulated EGR activity and non-significantly increased unstimulated EGR activity [30], but EGRAC values were lacking.…”
Section: Discussionsupporting
confidence: 92%
“…We hypothesized that the single bout of exercise could affect vitamin B2 status as determined by EGRAC, as the short-term effects (<24 h) of exercise on EGR activity have been reported by previous studies [21,28,30]. We also hypothesized that the EGRAC values after the single bout of exercise would be higher, i.e., vitamin B2 status would be lower in high-fit compared to low-fit individuals, as regular aerobic exercise enhances vitamin B2-dependent processes that could increase vitamin B2 demand.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Some authors believe that it does (14,15), whereas other authors do not (16)(17)(18). To ascertain if exercise increases the requirement of vitamin B1, we investigated whether the concentrations of vitamin B1 in the liver and blood were reduced when rats were forced to exercise on alternate days after being fed a diet containing a sufficient amount of thiamin (4.720 mg thiamin/ kg diet) or a diet containing a minimum requirement of thiamin (0.786 mg thiamin/kg diet).…”
Section: Discussionmentioning
confidence: 99%